THE EFFICIENCY OF THE USE OF PRIVATE MILITARY SECURITY COMPANIES (PMSC) BY THE UNITED STATES IN IRAQ - Raviq Ayusi (International Journal of Economics Management and Social Science, 2018)
The shift of security paradigm post-cold war era has made the concept of security more complex, regarding the actor and its scope. The security dynamic trigger the emergence of new non-state actors in the security field. Private Military Security Companies (PMSC) is one of a non-state actors that provides security services. The United States as a developed country makes use of this service not only during wartime but also on other certain condition. The choice of using PMSC services is considered to have greater efficiency than the use of state military.How efficient can the United States get by hiring the PMSC? Based on the analysis, this paper argues that the US efficiency by hiring the PMSC is quite high because of the ability of the US to see the conditions, taking into account further and minimize the impact that would come. This paper will outline through three components: international security governance, the efficient use of PMSC services, and the consideration more about the impact of the use of PMSC services.